PEMANFAATAN CITRA RESOLUSI TINGGI UNTUK KAJIAN KINERJA RUAS JALAN PADA POLA JARINGAN JALAN GRID KOTA SURAKARTA - , MIFTAHUL HANIFAH FITRIANINGRUM ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The performance of the road is affected by the road capacity as well as the traffic volume. Remote sensing data can provide detail information as a data source to know the road performance. This research aims at (1) studying the ability of QuickBird images in acquiring the road performance parameter and the traffic jam (2) knowing the road performance (3) knowing the effectiveness of the grid road network pattern in reducing the traffic jam. The method used in this research is based on the IHCM (Indonesian Highway Capacity Manual) 1997. The data of road wide and land use are acquired from the interpretation of QuickBird images. The traffic volume data are gained from the field survey. The traffic volume is gained by calculating the total of each type of vehicle at the peak hour. The peak hour is gained by counted daily traffic volume from CCTV recording. The road capacity is counted based on the formula in IHCM. The road performance is valued based on the level of service (LoS) which is the comparison between traffic volume and the value of road path capacity. The traffic management is gained based on the characteristics of the grid pattern. The traffic management is done to increase the LoS by decreasing the traffic volume or increasing the road capacity. The result of the study showed that the level of accuracy of land use interpretation is 96,29%, the level of accuracy of road geometric interpretation is 89,99%. The existing grid pattern is very effective in spreading the traffic volume. As a result, the LoS of Surakarta city is good in general. There is road path that need to be decreased concerning with the traffic volume in Jl. Ronggowarsito. The traffic managements which can be applied to reduce the traffic volume toward Jl. Ronggowarsito are by changing the traffic flow and restricting the means of transport.